Working more for less: Part-time penalties across the working hours distribution - Tom Günther; Ulrich Schneider; Fabian Stürmer-Heiber (Freie Universität Berlin, School of Business & Economics, 2023)
We use German administrative and survey data to investigate the heterogeneity of part-time penalties in hourly wages and growth rates. Exploiting tax reforms for identification, we find substantial heterogeneity in part-time wage penalties from -28.3% to -7.2% compared to full-time. The heterogeneity in wage growth penalties is less pronounced. Both penalties do not decrease linearly with additional working hours. More weekly working hours might result in a higher hourly wage penalty. The shape of the penalties is driven by workers with non-demanding tasks and professions where working around 30 weekly hours is uncommon, and relatively many females work.
urn:nbn:de:kobv:188-refubium-40852-6
Keywords: J16; J24; J31; 330; part-time employment; wage dynamics; female labor supply